Differences in mortality and causes of death between STEMI and NSTEMI in the early and late phases after acute myocardial infarction - Yasuaki Takeji (Public Library of Science (PLoS), 2021)
Background The detailed causes of death in non–ST-segment–elevation myocardial infarction (NSTEMI) have not been adequately evaluated compared to those in ST-segment elevation myocardial infarction (STEMI). Methods The study population was 6,228 AMI patients who underwent percutaneous coronary intervention (STEMI: 4,625 patients and NSTEMI: 1,603 patients). The primary outcome was all-cause death. Results Within 6 months after AMI, the adjusted mortality risk was not significantly different between NSTEMI patients and STEMI patients (HR: 0.83, 95%CI: 0.67–1.03, P = 0.09). Regarding the causes of death within 6 months after AMI, mechanical complications more frequently occurred in STEMI patients than in NSTEMI patients, while proportions of post resuscitation status on arrival and heart failure were higher in in NSTEMI patients than in STEMI patients. Beyond 6 months after AMI, the adjusted mortality risk of NSTEMI relative to STEMI was not significantly different. (HR: 1.04, 95%CI: 0.90–1.20, P = 0.59). Regarding causes of death beyond 6 months after AMI, almost half of deaths were cardiovascular causes in both groups, and breakdown of causes of death was similar between NSTEMI and STEMI. Conclusion The mortality risk within and beyond 6 months after AMI were not significantly different between STEMI patients and NSTEMI patients after adjusting confounders. Deaths due to post resuscitation status and heart failure were more frequent in NSTEMI within 6 months after AMI.